2020
DOI: 10.1108/pr-05-2019-0237
|View full text |Cite
|
Sign up to set email alerts
|

Perceived overqualification and counterproductive work behavior: testing the mediating role of relative deprivation and the moderating role of ambition

Abstract: PurposeThe purpose of this study was to test the mediating role of relative deprivation in the relationship between perceived overqualification and counterproductive work behavior. In addition to testing this mediation, the authors posited that ambition would interact with perceived overqualification to predict relative deprivation and, through it, counterproductive work behavior.Design/methodology/approachSurvey data collected from 181 employees were analyzed using the SPSS macro PROCESS to test the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 54 publications
2
31
2
Order By: Relevance
“…Although previous studies mostly believe that negative emotions can lead to negative results such as workplace counterproductive behavior and deviant behavior (Samnani et al, 2014). Connelly et al (2012) and Schreurs et al (2020) also propose there are some overlaps between knowledge hiding behavior and workplace counterproductive behavior. However, very limited empirical research exists on how negative emotion will affect individual knowledge hiding behaviors.…”
Section: Mediating Effect Of Negative Emotionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies mostly believe that negative emotions can lead to negative results such as workplace counterproductive behavior and deviant behavior (Samnani et al, 2014). Connelly et al (2012) and Schreurs et al (2020) also propose there are some overlaps between knowledge hiding behavior and workplace counterproductive behavior. However, very limited empirical research exists on how negative emotion will affect individual knowledge hiding behaviors.…”
Section: Mediating Effect Of Negative Emotionsmentioning
confidence: 99%
“…When negative emotions accumulate to a certain extent even exceed the control, negative emotions still have a negative impact on the individual's willingness to share knowledge. On the one hand, previous studies have shown that negative emotions can lead to personal workplace deviant behavior such as counterproductive behavior (Schreurs et al, 2020). Strong negative emotions increase the likelihood that employees abreact their negative emotions to their colleagues around them and even engage in displaced aggression behaviors (Samnani et al, 2014), which will cause tension among them.…”
Section: Mediating Effect Of Negative Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the existing research pays greater attention to the positive impact of perceived over-qualification on individuals, such as organizational citizenship behavior (Chen and Kao, 2011;Elamin and Tlaiss, 2015;Luksyte and Spitzmueller, 2016) and job satisfaction (Lee et al, 2013;Yang et al, 2015;Dong et al, 2020;García-Mainar and Montuenga-Gómez, 2020). Additionally, a few studies have explored the negative impact of perceived over-qualification on individuals, such as antiproductive behavior (Bolino and Feldman, 2000;Zhang et al, 2016;Schreurs et al, 2020). Second, there is limited research on the relationship between perceived over-qualification and turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…The P-E fit theory posits that there are five types of P-E fit, in which person-job fit is particularly important for individuals, especially in the workplace (Kristof-Brown et al, 2005;Jansen and Kristof-Brown, 2006;van Vianen, 2018). For instance, perceived overqualification (POQ), a typical type of person-job misfit in organizations (Erdogan et al, 2020) and a global trending phenomenon (Hu et al, 2015;Li et al, 2021;Zhang et al, 2021a), was proved from different theoretical perspectives that could rise many negative consequences in the workplace (Feldman, 1996;Harari et al, 2017), such as more counterproductive behavior (Liu et al, 2015;Schreurs et al, 2020), high turnover (Wu and Chi, 2020), less creative performance (Zhang et al, 2021b), and less proactive behavior (Luksyte et al, 2020). Furthermore, recent research has found that POQ leads to more cyberloafing in the organization (Cheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%